1987
DOI: 10.1016/s0022-5347(17)44053-5
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Testicular Size Measurement in Andrology: II. Correlation of Testicular Size with Testicular Function

Abstract: The testicular sizes of 305 men were measured by a recently developed orchidometer and related to 9 other known parameters of testicular function. Mean testicular size had the strongest correlation with serum follicle-stimulating hormone levels, total sperm count and sperm concentration, while a significant correlation also was noted with sperm motility, percentage of live sperm, sperm morphology (normal and immature forms), and serum luteinizing hormone and testosterone levels. Sperm quantity had stronger cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
100
5
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(118 citation statements)
references
References 2 publications
12
100
5
1
Order By: Relevance
“…It is therefore possible that the results of the meta‐analyses do not reflect the true picture. Each of the fertility measures assessed is also only a surrogate for true fertility, and although some, such as sperm count40 and morphology41, have been correlated with fertility, others, including testicular volume, number of germ cells present on testicular biopsy and testicular histology at the time of operation, have a less certain relationship10 42, 43, 44, 45. It is therefore impossible, from the studies included in this review, to draw any direct correlations between performing orchidopexy before 1 year of age and improved fertility.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore possible that the results of the meta‐analyses do not reflect the true picture. Each of the fertility measures assessed is also only a surrogate for true fertility, and although some, such as sperm count40 and morphology41, have been correlated with fertility, others, including testicular volume, number of germ cells present on testicular biopsy and testicular histology at the time of operation, have a less certain relationship10 42, 43, 44, 45. It is therefore impossible, from the studies included in this review, to draw any direct correlations between performing orchidopexy before 1 year of age and improved fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Testicular size is determined primarily by the mass of Sertoli cells and seminiferous tubules. The critical volume required for normal testicular function is estimated to be approximately 15 ml (6,7,9). Indeed, each of the four males that Bertelloni et al reported to have decreased testicular size, also had decreased sperm concentration and motility, elevated serum gonadotropins, but normal serum testosterone concentrations (4).…”
Section: Discussionmentioning
confidence: 99%
“…As the seminiferous tubules comprise approximately 90% of the testicular mass, testicular volume is largely a reflection of spermatogenesis [1,2]. Clinical studies in infertile men have also shown that testicular volume strongly correlates with semen profile [3].…”
Section: Introductionmentioning
confidence: 99%